INVESTIGATION OF THE FEASIBILTY OF USING CHIRP-EVOKED ABR IN ESTIMATION OF LOUDNESS GROWTH - Hoseingholizade, Sima (My University, 2015)
Loudness growth evaluation is important to comprehend the theoretical implication of loudness in both normal hearing and hearing impaired people, as well as applied applications in hearing-aid design. However, current psychoacoustic procedures are subjective, time consuming and require the constant attention of participants. The primary aim of the present study is to investigate the feasibility of objectively assessing the loudness growth function by using the Auditory Brainstem Response (ABR). Previous studies applied either non-frequency specific click stimuli or tone burst stimuli to evoke auditory brainstem responses. Although the advantage of a chirp stimulus in producing a more reliable response has been well documented in many studies, no one has previously used this stimulus to evaluate loudness growth functions. One octave-band chirp stimuli with center frequencies of 1000 Hz and 4000 Hz were chosen to evoke ABRs at 7 different stimulus intensities from 20 dB nHL to 80 dB nHL with 10 dB steps. In the psychoacoustic procedure, subjects were asked to rate the perceived loudness of each presented stimulus. The recorded ABR trials were averaged by a modified version of weighted averaging based on Bayesian inference. This method of averaging decreases the effects of non-stationary noise sources by calculating a number of locally-stationary noise sources based on a series of F-tests. The peak-to-trough amplitude of the most salient peak of the ABR at each intensity constituted the physiological loudness estimate. Linear and power functions relating the psychoacoustical results and the ABR measurements were compared. The obtained results were in good agreement with equal-loudness contours and estimated loudness from the loudness model for time-varying sounds of Glasberg, & Moore (2002). We concluded that loudness growth can be estimated with ABRs to frequency-specific chirp stimuli.
Keywords: Objective Loudness-Growth function